2021
DOI: 10.1016/j.transproceed.2020.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome in Human T-Lymphotropic Virus Type 2 Carriers Following Organ Transplantation

Abstract: Background. Frequent and rapid development of myelopathy has been reported in individuals with human T-lymphotropic virus type 1 (HTLV-1) infection following solid organ transplantation. There is no information regarding HTLV-2, a closely related virus that often infects injection drug users. Methods. This study includes a retrospective analysis of all consecutive organ transplants performed during the last 2 decades at a large reference transplantation unit in Spain. All participants were tested for anti-HTLV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…However, it was unknown whether these organs underwent confirmatory testing in the study by Shames et al, 11 and the number of organs rejected because of falsely positive initial screening tests was not reported in the UNOS data. In a retrospective analysis, 13 Though data from this study are comparable in number consistency with that reported by de Mendoza et al, 3 two donors were initially reactive (0.06%) with no evidence of HTLV infection and testing suggests false positive testing.…”
Section: According To the American Society Of Transplantation Infectioussupporting
confidence: 89%
“…However, it was unknown whether these organs underwent confirmatory testing in the study by Shames et al, 11 and the number of organs rejected because of falsely positive initial screening tests was not reported in the UNOS data. In a retrospective analysis, 13 Though data from this study are comparable in number consistency with that reported by de Mendoza et al, 3 two donors were initially reactive (0.06%) with no evidence of HTLV infection and testing suggests false positive testing.…”
Section: According To the American Society Of Transplantation Infectioussupporting
confidence: 89%
“…One presented a myopathy with histological confirmation 36 and another developed paraparesis following initiation of antiretroviral therapy to treat HIV‐1, resembling an immune reconstitution inflammatory syndrome 37 . It is noteworthy that clinical manifestations potentially associated to HTLV‐2 does not develop in the transplantation setting, where large inoculum size and immunosuppression might potentiate viral pathogenicity 38 …”
Section: Htlv‐2 Epidemicsmentioning
confidence: 99%
“…37 It is noteworthy that clinical manifestations potentially associated to HTLV-2 does not develop in the transplantation setting, where large inoculum size and immunosuppression might potentiate viral pathogenicity. 38 During 2022, six new cases of HTLV-2 were reported in Spain.…”
Section: Htlv-2 Epidemicsmentioning
confidence: 99%